Study on discharge characteristics and improving surface hydrophobicity of epoxy resin by nanosecond pulse excited argon/hexamethyldisiloxane jet array. (23rd February 2022) - Liu, Zhiyan; Xu, Jingang; Zhu, Xi; Liu, Feng; Fang, Zhi
Abstract: Surface flashover of insulating materials induced by pollution and moisture environment is one of the main reasons for the damage of power system and electrical equipment. The improvement of the insulating materials surface hydrophobicity is key important, which can prevent the pollutants and water attachment, and enhance the insulating performance. In this paper, the super‐hydrophobic film is formed on the surface of epoxy resin by a one‐dimensional (1D) argon (Ar) jet array driven by nanosecond pulse power supply with hexamethyldisiloxane (HMDSO) addition. The influences of the processing time and HMDSO content on the epoxy resin surface hydrophobicity are investigated. It shows that with 0.04 % HMDSO, the jet array achieves a best hydrophobic treatment effect on the epoxy resin surface. After 60 s treatment, the apparent contact angle (ACA) of the epoxy resin surface increases from 60.3° of the untreated surface to 150.0°. The wettability of epoxy resin surface does not change too much as the treatment time beyond 60 s. The maximum ACA value 153.4° appears at 120 s processing time, which is just slightly higher than that of 60 s treatment time. The epoxy resin surface morphology and chemical feature before and after plasma processing are characteristics by the scanning electron microscopy (SEM), atomic force microscopy (AFM), Fourier transform infra‐red spectroscopy and X‐ray photoelectron spectroscopy. It shows that the treated epoxy resin surface is covered with dense coral like particles in nanoscales, the original C=O、C‐H and other organic functional groups are replaced by Si‐(CH3 ), Si‐O‐Si and other silicon containing groups, and the Si content increases from 0.4% to 28.0%. The experimental results provide important references to develop jet array as an efficient tool to enhance the surface hydrophobicity and insulating performance of insulating materials.